(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
One of obstacles in cultivation of lobster Panulirus homarus is availability of lobster seeds in same size. Nursery with a recirculation system is an alternative technology that can be used to make seed in same size. The aim of this study to evaluate the growth performance and water quality of lobster P. homarus reared by using a recirculation system. Research design consisted of 4 treatments and 2 repetation, namely control tank (K) using a flow trough system, treatment tank (SK) equipped with a skimmer, treatment tank (F) equipped with a trickle filter, treatment tank (SKF) equipped with a skimmer and trickle filter. The results showed that the daily growth rate (LPH) and FCR were not significantly different in all treatments (P>0.05). The highest weight was obtained from the control 1.09 g and the highest length in treatment SK was 3.58±0.09 cm. Temperature was relatively stable at 25.6–27.1oC, DO 4.6–6.3 mg/L, salinity 33.4-37.4 ppt, TDS 33.5–36.9 mg/L, pH 7.6–7.9, nitrite (NO2) levels ranged from 0.03 to 4.1 mg/L. The value of nitrate (NO3) during study ranged from 0.9 to 15.5 mg/L. The value of ammonia (NH3) ranged from 0.001 to 0.049 mg/L. Filtration system (skimmer and trickle filter) treatment was able to provide optimal water quality for lobster growth.